METHODOLOGICAL ASPECTS OF COMPETENT APPROACH TO DEVELOPING THE CREATIVITY OF STUDENTS IN THE FUTURE PROFESSIONAL PEDAGOGICAL HIERARCHY OF PHYSICAL CULTURE EDUCATION - Eshqobilov Elmurod Menglimurod o’g’li (Journals Park Publishing, 2024)
In this article, the work carried out by the authors to improve their pedagogical skills and opportunities based on a competent approach in order to become quality and mature pedagogues in the future, as well as the shortcomings in these works, is the current problem, as well as the solution to this problem. proposals and comments aimed at.
Keywords: Competent, physical education, pedagogue, expert, education, quality, profession, training, competence, ability, creativity, qualification, formation, development and method.